2011
DOI: 10.1111/j.1475-2743.2011.00376.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in uranium and thorium contents in topsoil after long‐term phosphorus fertilizer application

Abstract: Archived soil samples from the beginning and end of three long‐term field trials conducted in central France were analysed for total uranium (U) and thorium (Th) contents to evaluate the effect of 15–30 yr of phosphorus (P) fertilizer treatments on the accumulation of these elements in the topsoil. For comparison, the soil samples were also analysed for total P. Three treatments were compared: no P application (P0), 26 kg P/ha/yr (P26) and 52 kg P/ha/yr (P52). Significant effects of P fertilizer were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 22 publications
1
14
1
Order By: Relevance
“…The most contaminating industries are U mining and milling, metal mining and smelting, and the phosphate industry (Vandenhove, ). Agricultural phosphate fertilization also accounts for a major source of U dissemination (Schipper et al ., ; Wetterlind et al ., ). In its soluble form, U may be taken up by plants and can therefore contaminate the food chain (Neves et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The most contaminating industries are U mining and milling, metal mining and smelting, and the phosphate industry (Vandenhove, ). Agricultural phosphate fertilization also accounts for a major source of U dissemination (Schipper et al ., ; Wetterlind et al ., ). In its soluble form, U may be taken up by plants and can therefore contaminate the food chain (Neves et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Phosphate fertilizers contain different levels of radioisotopes and have long been identified as a possible source of uranium in the environment (e.g. Barišić et al, 1992;Guimond and Windham, 1975;Guimond and Hardin, 1989;Hamamo et al, 1995;Pfister et al, 1976;Wetterlind et al, 2012;Zielinski et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For soils with high clay and organic-matter content, U is anticipated not to migrate substantially (Rogasik et al, 2008). Accordingly, several studies have shown that long-term fertilization with mineral based P-fertilizers leads to substantial accumulation of U in soils, particularly topsoil, compared to unfertilized soils (Bigalke et al, 2017;Jones, 1992;Rogasik et al, 2008;Schipper et al, 2011;Takeda et al, 2005Takeda et al, , 2006Taylor, 2007;Wetterlind et al, 2012;Yamaguchi et al, 2009;Zielinski et al, 2006). In accordance with these findings, a number of authors have pointed to regional variations in concentrations of U in drinking water generally related to bedrock composition, even if the direct relationship might be complicated by groundwater flow through different rock formations (CCME, 2011;Stalder et al, 2012).…”
Section: Introductionmentioning
confidence: 99%